O batismo e a eucaristia na perspectiva da deificação - Savelli, Pedro (2011)
Deification: in the ecstatic love of God we are deified to be in communion with His life and nature. The Perspective of the Deification opens three paths for the human being to be conscious of taking part of the divine nature: a) through the way of Life. We only exist by virtue of the kindness of God. Out of nothing, He calls everything to the light: the work of the Creation expresses the Will of God, everything belongs to Him and from Him receives the natural deification; b) through the way of Revelation. The people from Israel knew how to interpret its own history as a singular election of God, whose objective is to be the light to the nations: deification by the obedience to the listening of the Word of God. c) Through the way of Grace: Reincarnation and Glorification of the Christ-Sacrament. Father God, in the mystery of His donation to the humanity, invites us to participate in His divine nature, transformed by the Son in the strength of the Hole Spirit: covering us of Christ by the Baptism and feeding us from Him by the Eucharist: sacramental deification. In Christ, Head, the Church is Sacrament. It updates the deifying Grace through the Spirit, celebrating the liturgy, particularly, the Eucharist: it is in the latter that we find ourselves